Serum IL-6, IL-10, TNF-α changes after of manual lymphatic drainage combined with abdominal breathing in the rehabilitation of postpartum perineal edema : Serum IL-6, IL-10, TNF-α after Postpartum - Xue, Lili (Journal of Medical Biochemistry, 2025)
Objective: This study aims to evaluate the effectiveness of manual lymphatic drainage (MLD) combined with abdominal breathing in the rehabilitation of postpartum perineal edema and Serum IL-6, IL-10, TNF-α.Methods: A total of 172 primiparous women who delivered in our hospital between January 2022 and June 2023 were randomly assigned to either the observation group (n=86) or the control group (n=86). The control group received routine midwifery care, while the observation group received additional MLD and abdominal breathing training. Outcomes measured included pain levels, induration diameter, comfort, emotional state, recovery time, and clinical efficacy. Inflammatory markers, including C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), interleukin-6 (IL-6), interleukin-10 (IL-10), and tumor necrosis factor-alpha (TNF-α), were also assessed.Results: Both groups demonstrated significant reductions in Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS) scores after treatment (P
Keywords: CRP, ESR, IL-6, IL-10, TNF-α, natural childbirth, perineal edema, manual lymphatic drainage, abdominal breathing, postpartum recovery